Spin-wave wavelength down-conversion at thickness steps. (3rd April 2018) - Stigloher, Johannes; Taniguchi, Takuya; Madami, Marco; Decker, Martin; Körner, Helmut S.; Moriyama, Takahiro; Gubbiotti, Gianluca; Ono, Teruo; Back, Christian H.
Abstract: We report a systematic experimental study on the refraction and reflection of magnetostatic spin-waves at a thickness step between two Permalloy films of different thickness. The transmitted spin-waves for the transition from a thick film to a thin film have a higher wave vector compared to the incoming waves. Consequently, such systems may find use as passive wavelength transformers in magnonic networks. We investigate the spin-wave transmission behavior by studying the influence of the external magnetic field, incident angle, and thickness ratio of the films using time-resolved scanning Kerr microscopy and micro-focused Brillouin light scattering.